Competition, efficiency and soundness in European life insurance markets - Cummins, J. David; Rubio-Misas, María; Vencappa, Dev (Journal of Financial Stability, 2017)
This paper provides cross-country evidence on the association between soundness and competition in the life insurance industry, where competition is measured by the Boone indicator. We analyse 10 European Union (EU) life insurance markets over the post-deregulation period 1999–2011. The results indicate that competition increases the soundness of the EU life insurance markets. Since the Boone indicator measures competition based on the reallocation of profits from inefficient insurers to efficient ones, our results suggest that efficiency is the mechanism through which competition contributes to insurer solvency. The soundness-enhancing effect of competition is greater for weak insurers than for healthy ones.